PEMBELAJARAN MATEMATIKA BERBASIS PMRI SISWA KELAS VIII NEGERI 3 SUSUA - Ratio Julianci Simarmata (Universitas Sriwijaya, 2022)
Lack of interest in student learning, limited learning media is one of the problems in mathematics. For this reason, PMRI is considered a solution that is able to overcome these obstacles. The purpose of this study is to see whether the learning carried out at SMP Negeri 3 Susua is in accordance with the principles and characteristics of PMRI (Indonesian realistic mathematics learning). This type of research is descriptive qualitative. For the research subject is class VIII SMP with research instruments observation sheets, documentation and questionnaires. The conclusion drawn from this study is that the learning carried out in class VIII of SMP Negeri 3 Susua is in accordance with the principles and characteristics of the PMRI.